PENGARUH TERAPI RELAKSASI AUTOGENIK TERHADAP TINGKAT KUALITAS TIDUR PADA LANJUT USIA - Mira Anggraini; Arneliwati Arneliwati; Yesi Hasneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
The elderly will experience a decrease in body condition and function; a decrease in the quality of sleep characterized by insomnia. Decreasing the quality of sleep can cause a decline in the life expectancy of the elderly. One therapy that can overcome the sleep needs of the elderly is by means of autogenic relaxation therapy. This research aimed to determine the effect of autogenic relaxation on sleep quality in the elderly. This research used the Quasy Experiment method with the design of the Non-Equivalent Control Group. The research population was 69 people of PSTW Khusnul Khotimah Pekanbaru. The research respondents were 30 respondents who were obtained by Purposive Sampling techniques that were in accordance with the inclusion criteria in the study. The instrument of data collection used an insomnia questionnaire. Autogenic relaxation was given for 3 days with in 20 minutes every meeting. Data analysis used was Wilcoxon Signed Ranks. The results of the study were the average age of the respondents in the old age range (60-90), the majority of respondents were female 52.9% and respondents who were Muslim were 97.1%. the Wilcoxon Signed Ranks the results show that p value 0,000 (p < α). This research concluded that there was an influence between autogenic relaxation on sleep quality in the elderly. This autogenic therapy can be applied by the elderly as an independent intervention on the quality of sleep. Keywords: Autogenic, elderly sleep, quality